CHARACTERISTICS OF THE EFFICIENT TEACHING. RESULTS OF AN ASCERTAINED STUDY - DANA JUCAN (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. The aim of our approach was to investigate and outline to a realistic educational level the existent situation regarding the general opinions of the teachers upon the efficient teaching. We intended to discover, the characteristics of an efficient teaching, methods used by teachers to discuss and systemise information during courses and seminars, the stimulation degree of the students' reflexivity during courses and seminars, modalities to facilitate the absorption of information by the students, the claim to note taking during courses/seminars.